Problem of variability and stability in language/dialect - Jutronić, Dunja (Array, 2019)
1. I present my research of the changes in the Split dialect (4 chosen syntactic variables): a. Construction “of + genitive” (prsten od zlata – ‘a ring of gold’) instead of the adjectival attribute as in zlatni prsten (‘a golden ring’); b. The mixing of locative and accusative. An example of this feature would be the following sentence: Bija san u Split instead of Bija san u Splitu (‘I was in Split’). The second sentence has the correct locative ending –u; c. Contraction of mi je >me. The phrase Draga mi je Ravena is contracted into Draga me Ravena (‘Ravena is dear to me’); d. Čakavian dialect got its name from the interrogative-relative pronoun ča (example: Ča radiš? – ‘What are you doing?’) which is being replaced by the standard form što/šta. 2. I try to answer the question: What is left of the Split dialectal syntax? Why did some dialectal variables disappear, why are some in the state of variation and others still firmly used in this urban vernacular? The principle of salience is used as a theoretical tool for the explanation of the present trend in dialect change. 3. Finally, and most importantly, on the basis of my research I try to say something about the problem of variability and stability in language which is discussed in the philosophy of language. Namely, a view has been put forward by Georges Rey (2006) that standard linguistic entities (like phonemes, morphemes, etc.) do not exist, that they are intentional inexistents. One of the problems for the existence of linguistic entities is variability witthin a speech community. Rey tries to press the point that variability is a major (if not the crucial) problem in identifying standard linguistic entities (SLE’s). The same question can be asked about dialects. Is variability a problem for their identification and existence? I argue and try to show that variability is not the problem.